ESL Models and their Application Electronic System Level Design and Verification in Practice - Bailey, Brian. (Embedded Systems, 2010)
ESL Models and their Application: Electronic System Level Design and Verification in Practice Grant Martin Brian Bailey This book arises from experience the authors have gained from years of work as industry practitioners in the field of Electronic System Level (ESL) design and verification. At the heart of all things related to Electronic Design Automation (EDA), the core issue is one of models: what are the models used for, what should the models contain, and how should they be written and distributed. Issues such as model interoperability and transportability become central factors that may decide which models and tools are successful and those that cannot get sufficient traction in the industry to survive. Through a set of real examples taken from recent industry experience, this book distills the state-of-the-art of System-Level models and provides practical guidance to readers that can be put into use. This book is an invaluable tool that will aid readers in their own designs, reduce risk in development projects, expand the scope of design projects, and improve developmental processes and project planning. Provides insight to all phases of ESL model design and flow for novices, students, researchers, managers, and experienced hardware and software designers and architects; Includes extensive, realistic examples from industrial ESL design flows; Focuses on the models that are the cornerstone of those flows and provides concrete examples showing how they are created, how they are used and the how they get transformed. This book is a must-have for anyone needing to understand the essentials of system-level models: their purpose, their contents, and how they should be created and distributed.